Robust design proposal by the use of structural topology optimization considering uncertainties of input parameters and boundary conditions - Stangl, Thomas; Walter, Michael; Wartzack, Sandro; Schneyer, Thomas (Proceedings of the 19th International Conference on Engineering Design, 2013)
Specifying a product's optimal mechanical and functional design primary depends on the requirements defined by the future operating conditions. In today's product design process the usage of topology optimization is a widely applied computer aided method to define an optimal design considering these requirements. However, in an early design stage, input parameters for this structural optimization process (e.g., operation conditions) are usually uncertain. Consequently, the resulting design is not optimal. This paper focuses on a detailed investigation of uncertainties in structural topology optimization. Hence, the different kinds of uncertainties and their effects on the resulting designs are considered in detail. Furthermore, a methodology is presented, which enables the consideration of uncertainties using e.g., a statistical investigation of the topology optimization results and a sensitivity analysis-based result visualization. Therefore, a cam drive rocker arm of a combustion engine is analyzed in a case study. Finally, several recommendations are derived, supporting the product developer to define a robust initial design, causing less computational and time expense.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.robust
Keywords: Design engineering; Early functional validation; Optimisation; Robust design; Uncertainty in topology optimization